2014
DOI: 10.1108/mi.2014.5354
|View full text |Cite
|
Sign up to set email alerts
|

Art therapy: an underutilized, yet effective tool

Abstract: Art therapy has been recognized as beneficial and effective since first described by Adrian Hill in 1942. Even before this time, art therapy was utilized for moral reinforcement and psychoanalysis. Art therapy aids patients with, but not limited to, chronic illness, physical challenges, and cancer in both pediatric and adult scenarios. Although effective in patient care, the practice of art therapy is extremely underutilized, especially in suburban areas. While conducting our own study in northeastern Ohio, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Although participants had some difficulties implementing ReAT at the elementary school level, the school counselors described numerous benefits with this novel approach that align with reality therapy literature, including enhanced relationship building, improved insights and skills gained by students, and development of problem-solving strategies (Davis & Clark, 2012; Mason, 2016). These findings also coincide with literature noting the importance of such aspects in the quality of school engagement for students with chronic conditions (Bitonte & DeSanto, 2014; Boles, 2017; Gan et al, 2017; Janin et al, 2018; Lum et al, 2017; Merianos et al, 2015; Pedigo et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although participants had some difficulties implementing ReAT at the elementary school level, the school counselors described numerous benefits with this novel approach that align with reality therapy literature, including enhanced relationship building, improved insights and skills gained by students, and development of problem-solving strategies (Davis & Clark, 2012; Mason, 2016). These findings also coincide with literature noting the importance of such aspects in the quality of school engagement for students with chronic conditions (Bitonte & DeSanto, 2014; Boles, 2017; Gan et al, 2017; Janin et al, 2018; Lum et al, 2017; Merianos et al, 2015; Pedigo et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Art therapy has been identified as an effective, creative, and developmentally appropriate technique to help children explore situations that may be too painful or confusing to discuss while encouraging self-exploration, awareness, and growth (Cook, Mayorga, & Ball, 2016; Pielech, Sieberg, & Simons, 2013). In particular, art therapies have been shown to be effective in helping children facing chronic conditions reduce stress, enhance problem-solving skills, and develop a strong sense of well-being (Bastemur, Dursun-Bilgin, Yildiz, & Ucar, 2016; Beebe, Gelfand, & Bender, 2010; Bitonte & DeSanto, 2014; Palmer & Shepard, 2008). Further, art therapies fit well with the ASCA National Model for responsive services and lend themselves to combination with other counseling approaches (e.g., reality therapy) and application in school settings (Gonzalez-Dolginko, 2018; Losinski, Hughley, & Maag, 2016; Randick & Dermer, 2013).…”
Section: Art and Reality Therapy In Schoolsmentioning
confidence: 99%
“…Interestingly, it has also been found that ethnic minority groups, who typically report poorer quality of life and worse distress after diagnosis, may derive more acute benefit from integrated modalities like art therapy [88]. It is also of importance to note that effective psychosocial support programs have been shown to be significantly associated with favorable clinical outcomes [84,[89][90][91][92].…”
Section: Clinical Considerations Of a Growing Cohort Of Long-term Surmentioning
confidence: 99%
“…2 However, there is limited literature evaluating art therapy in child and adolescent mental health services (CAMHS) units. 3 In mental health inpatient settings, verbal therapies continue to dominate. 2 However, many inpatients are unable to verbalise their concerns, and say they feel nothing or are numb.…”
Section: Psychiatrymentioning
confidence: 99%
“…2 However, there is limited literature evaluating art therapy in child and adolescent mental health services (CAMHS) units. 3…”
mentioning
confidence: 99%